Legal Status of Duplicate Land Certificates and Mechanisms for Their Resolution Under the National Land Law System - Christhopher, Michael; Djaja, Benny (Jurnal Ilmu Hukum Kyadiren, 2026)
This study examines the legal status of duplicate land certificates for the same parcel and the mechanisms available for resolving such issues within the Indonesian land law system. Employing a normative juridical method with statutory, conceptual, and case-study approaches, the study evaluates the validity of certificate issuance, procedural compliance, and the evidentiary basis used to determine the rightful owner. The findings show that duplicate certificates typically arise from inconsistencies between physical and legal records, procedural irregularities, or unlawful actions during the land registration process. Resolution may be pursued through administrative procedures at the National Land Agency (BPN) or through litigation in administrative, civil, or criminal courts. Administrative procedures enable the correction or annulment of certificates issued with procedural defects, whereas litigation provides legal certainty in disputes over substantive rights or allegations of forgery. The study underscores the need for greater integrity in the certificate issuance process, as well as enhanced coordination and law enforcement to prevent the occurrence of duplicate certificates.